Arbitrary pole placement with the extended Kautsky–Nichols–van Dooren parametric form - Schmid, R.; Ntogramatzidis, Lorenzo; Nguyen, T. (Taylor & Francis, 2016)
We consider the classic problem of pole placement by state feedback. The well-known eigenstructure assignment algorithm of Kautsky, Nichols, and van Dooren is extended to obtain a parametric formula for the pole-placing feedback matrix that can deliver any desired closed-loop eigenvalues, with any desired multiplicities.